Appendix 1.5: “Nine-Hole Golf Course Is New Attraction on University Campus,” Diliman Star, 25 October 1952 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Marcos maintained ties with the University of the Philippines even when he was still in Congress. He was once president of the University of the Philippines Alumni Association, a position that has usually been held by Upsilon Sigma Phi fraternity brothers such as Marcos. Other Upsilonians include UP Board of Regents member Magdaleno Albarracin and UP President Alfredo Pascual.